A Counterintuitive Argument for Résumé Embellishment - Marcoux, Alexei M. (Journal of business ethics, 2006)
Applied ethicists say little about résumé embellishment. Presumably, this is so because résumé embellishment seems obviously wrong; an instance of ordinary lying, familiar moral prohibitions against which cover the case completely. Analysis of résumé embellishment merely as ordinary lying overlooks its collective action aspects. Taking account of those aspects and their implications, I argue on consequentialist grounds that, given some plausible background conditions, a limited form of résumé embellishment is morally permissible (and perhaps required). This outcome is a particular instantiation of a more general principle about how one ought to act when participating in a morally valuable co-ordinative practice. I conclude by identifying implications for how employers ought to use résumés in hiring decisions.